Women Entrepreneurship in MSME’s in Rajasthan: A study Jaipur Region (International Journal of Food and Nutritional Sciences, 2022)
The study will be confined to analyse the women entrepreneurs working in Micro, Small and Medium Enterprises in Jaipur region of Rajasthan. This paper has given emphasis on prospects and challenges of women entrepreneurship in Jaipur district of Rajasthan. The population of the study consists of registered and unregistered women entrepreneurs. A sample of 50 women entrepreneurs are selected for the study on the basis of Judgemental sampling. This paper has to explore the hidden prospects of women entrepreneurship and also forwarded some suggestions in improvement of women entrepreneurship in Jaipur district of Rajasthan.